The Hip Sports Activity Scale for patients with femoroacetabular impingement syndrome—Validation in Swedish. Issue 4 (29th March 2019) - Öhlin, Axel; Jónasson, Páll; Ahldén, Mattias; Thomeé, Roland; Baranto, Adad; Karlsson, Jón; Sansone, Mikael
Abstract : Purpose: To translate and culturally adapt the Hip Sports Activity Scale (HSAS) to Swedish and validate the Swedish version in patients with femoroacetabular impingement (FAI) syndrome. Materials and Method: The original German version was translated to Swedish. To determine reliability, validity, and floor and ceiling effects, a questionnaire set consisting of the Swedish version of the HSAS, the Copenhagen Hip and Groin Outcome Score (HAGOS), the short version of the international hip outcome tool, and the Tegner Activity Scale was completed pre‐operatively by 30 patients planned for arthroscopic hip surgery for FAI syndrome. To determine responsiveness, pre‐operative and one‐year follow‐up HSAS data from 30 patients treated with arthroscopic hip surgery for FAI syndrome were collected. Results: For test‐retest reliability, the interclass correlation was 0.930. The HSAS correlated to the Tegner score ( r  = 0.794, P  < 0.01), as well as to the HAGOS subscale of "physical activity" ( r  = 0.436, P  < 0.05). Cohen's effect size and the standardized response mean were 0.25 and 0.28, respectively. Ceiling and floor effects were between 7% and 10%. Conclusion: The Swedish version of the HSAS is a reliable and valid measurement to determine sports activity levels in patients with FAI syndrome.